A home‐based, primary‐care model for epilepsy care in India: Basis and design. Issue 2 (6th March 2019) - Singh, Gagandeep; Sharma, Suman; Bansal, Rajnder K.; Setia, Raj K.; Sharma, Sarit; Bansal, Namita; Chowdhury, Anuraag; Goraya, Jatinder S.; Chatterjee, Susmita; Kaur, Sukhpreet; Kaur, Manpreet; Kalra, Shivani; et al.
Summary: Objectives: A cluster‐randomized trial of home‐based care using primary‐care resources for people with epilepsy has been set up to optimize epilepsy care in resource‐limited communities in low‐ and middle‐income countries. The primary aim is to determine whether treatment adherence to antiepileptic drugs is better with home‐based care or with routine clinic‐based care. The secondary aims are to compare the effects of the two care pathways on seizure control and quality of life. Methods: The home‐based intervention comprises epilepsy medication provision, adherence reinforcement, and epilepsy self‐management and stigma management guidance provided by an auxiliary nurse‐midwife equivalent. The experimental group will be compared to a routine clinic‐based care group using a cluster‐randomized design in which the unit of analysis is a cluster of 10 people with epilepsy residing in an area cared for by a single accredited government grass‐roots health care worker. The primary outcome is treatment adherence as measured by monthly tablet counts supplemented by two self‐completed questionnaires. The secondary outcomes include monthly seizure frequency, time to first seizure (in days) after enrollment, proportion of patients experiencing seizure freedom for the duration of the study, and quality of life measured by the "Personal Impact of Epilepsy Scale, " all assessed by an independent study nurse. Results: The screening phase and neurologic evaluations and randomizations have been recently completed and follow‐up is underway. Significance: The results of the trial are likely to have substantial bearing on the development of governmental policies and strategies to provide coverage and care for patients with epilepsy in resource‐limited countries.